Do Relationships Matter? Evidence from Loan Officer Turnover - Drexler, Alejandro; Schoar, Antoinette (Management Science, 2014)
We show that the cost of employee turnover in firms that rely on decentralized knowledge and personal relationships depends on the firms' planning horizons and the departing employees' incentives to transfer information. Using exogenous shocks to the relationship between borrowers and loan officers, we document that borrowers whose loan officers are on leave are less likely to receive new loans from the bank, are more likely to apply for credit from other banks, and are more likely to miss payments or go into default. These costs are smaller when turnover is expected, as in the case of maternity leave, or when loan officers have incentives to transfer information, as in the case of voluntary resignations. This paper was accepted by Wei Jiang, finance.